2019
DOI: 10.1039/c9cc04627e
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic synthesis at impact craters: the role of Fe-clays and iron meteorites

Abstract: Iron-rich smectites formed by reprocessing of basalts due to the residual post-impact heat could catalyze the synthesis and accumulation of important prebiotic building blocks such as nucleobases, amino acids and urea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…These experiments show that PO 4 3− was widely available to prebiotic chemistry and nascent life on early Earth and potentially on other planets. It should be noted that our previous work demonstrates that water iron-rich smectites likely produced by water alteration of meteoritic material are plausible catalysts for the thermal synthesis of canonical nucleobases, hypoxanthine, purine, urea and glycine [29]. The synthetic potential of formamide as a prebiotic feedstock molecule was reported by the Saladino and Di Mauro groups and confirmed by other studies [73].…”
Section: Influence Of Ammonia (Nh3) Environment On Zncd Qds Emission supporting
confidence: 81%
See 1 more Smart Citation
“…These experiments show that PO 4 3− was widely available to prebiotic chemistry and nascent life on early Earth and potentially on other planets. It should be noted that our previous work demonstrates that water iron-rich smectites likely produced by water alteration of meteoritic material are plausible catalysts for the thermal synthesis of canonical nucleobases, hypoxanthine, purine, urea and glycine [29]. The synthetic potential of formamide as a prebiotic feedstock molecule was reported by the Saladino and Di Mauro groups and confirmed by other studies [73].…”
Section: Influence Of Ammonia (Nh3) Environment On Zncd Qds Emission supporting
confidence: 81%
“…Equally, sulfur chemistry was typical for hydrothermal vents on early Earth. In some impact structures, the metal content was enhanced with the addition of thiols and NH 3 [29]. These structures were also subjected to alteration by liquid water.…”
Section: Resultsmentioning
confidence: 99%
“…As was mentioned in the Introduction, hypoxanthine was detected by Ferus et al [ 12 ] and by Enchev et al [ 13 ] by heating pure formamide at 160°C for 24 hours and at 140°C for 2 weeks, respectively. Here, we suggest a formamide/formimidic acid‐catalytic mechanism of hypoxanthine formation from urea, formic acid, and glycinamide.…”
Section: Discussionmentioning
confidence: 95%
“…[ 10 ] Barks et al [ 11 ] obtained a very small quantity of hypoxanthine through a purely thermal process, heating neat formamide to 130°C. Quite recently, Ferus et al [ 12 ] and Enchev et al [ 13 ] observed canonical RNA nucleobases, hypoxanthine, urea, and the amino acid glycine heating pure formamide.…”
Section: Introductionmentioning
confidence: 99%
“…The typical thermal formamide-based synthesis is depicted in Figure 4. This mechanism is also very plausible in post-impact hydrothermal environment with metal-rich water altered minerals containing both original material from the impactor and formamide likely produced in the early planetary environment [201]. Formic acid, HCOOH, is often overlooked in prebiotic synthesis, even though it was a major product in the famous Miller-Urey experiment.…”
Section: State Of the Art: Prebiotic Synthesismentioning
confidence: 99%